ANALYSIS OF FACTORS THAT INFLUENCE THE CAPITAL STRUCTURE IN FOOD AND BEVERAGES - Nawarcono, Winanto (Accounting, 2010)
Simultaneous test results showed that the value of f-calculate equal to 10.421 with a significance of 0.000 is smaller than the expected level of significance of 5%, which means that the asset structure, firm size, profitability, sales growth and operating leverage simultaneously affect the capital structure. Thus the formulation of hypotheses based on test results is sure. While sixth beta coefficient of 0.508, the structure of assets is an independent factor that most affects the capital structure as the dependent factor, because the beta coefficients are owned asset structure is the largest beta coefficient when compared with the beta coefficient of company size factor amounted to 0.262, the factor of 0.109 profitability, sales growth factor of 0.120, and the operating leverage factor of 0.112. so that the formulation of hypothesis seven unanswered. Keyword : Capital Stucture, Food, Baverages